Pengaruh Brand Ambassador terhadap Brand Awareness Tokopedia (Studi Pada Iklan Tokopedia feat BTS Pada Masyarakat Kota Denpasar) - Elfani Wijaya, Catherine; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Tokopedia is one of the e-commerce in Indonesia that uses Brand Ambassador in commercial as their marketing strategy. Tokopedia appointed BTS, a boyband group from South Korea, as their Brand Ambassador since 2019. This study aims to find out the influence of Brand Ambassador BTS towards Brand Awareness of Tokopedia which focused on Tokopedia feat BTS commercial with Stimulus Organism Responds theory. This study using quantitative descriptive research with the data obtained from 100 respondents from age 16 to 34 years old in Denpasar City. The analysis shows that H 1 accepted that Brand Ambassador BTS has influence towards Brand Awareness of Tokopedia. Furthermore, the coefficient value showed that 46,2% of Tokopedia’s Brand Awareness was influenced by BTS as their Brand Ambassador and that value categorized as medium category. The results of the Brand Awareness average variable showed, that the highest average of brand recognition indicator is 4,41. Keywords : Brand Ambassador, BTS, Brand Awareness, Tokopedia